PENGARUH REKRUTMEN, SELEKSI, PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP RETENSI KARYAWAN NON-NAKES DI RS X - Hayati, Mahrida; Hasymi, Liana Fitriani (LPPM Universitas Awal Bros, 2025)
Employee retention has become a major challenge in human resource management within hospitals, including for non-medical staff. A high turnover rate can disrupt the operational stability of a hospital. Therefore, human resource management strategies such as recruitment, selection, training, and career development are considered essential to improve employee retentio. This study aims to analyze the influence of recruitment, selection, training, and career development on the retention of non-medical employees at RS X. This research applied a quantitative approach with a cross-sectional design. The sample consisted of 60 non-medical employees selected through total sampling. Data were collected using a Likert-scale questionnaire and analyzed using Spearman rank correlation and logistic regression. Partially, the variables of recruitment, selection, training, and career development have a significant influence on the retention of non-medical employees at RS X. However, simultaneously, the selection variable does not show a significant effect on employee retention. Recruitment has a significant influence on the retention of non-medical employees at RS X, both partially and simultaneously. Selection has a partial influence on employee retention but does not have a significant simultaneous effect. Training significantly influences employee retention both partially and simultaneously. Career development also has a significant influence on employee retention, both partially and simultaneously